2021
DOI: 10.1016/j.talanta.2020.122079
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Solids Analysis Probe (ASAP) and Atmospheric Pressure Gas Chromatography (APGC) coupled to Quadrupole Time of Flight Mass Spectrometry (QTOF-MS) as alternative techniques to trace aromatic markers of mineral oils in food packaging

Abstract: The aim of this work was to select and identify the best markers of aromatic hydrocarbon mineral oil (MOAH) in food packaging. For this purpose, a series of mineral oils was initially analysed. Polycyclic Aromatic Hydrocarbons (PAHs) and the alkylated isomers of Methylnaphthalene (MNS), Diisopropylnaphtalene (DIPNs), Dibenzothiophenes (DBTS), Methyldibenzothiophene (MDBTs), Dimethyldibenzothiophenes (DMDBTs) and Benzonaphthiophenes (BNTS) were then explored. Their presence was confirmed by direct analysis of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The substances used as target analytes in this study were proposed in a previous study as MOAH markers (Jaén et al, 2021). Furthermore, these substances were identified by different authors in mineral and crude oil samples.…”
Section: Selection Of Moah Markersmentioning
confidence: 95%
See 2 more Smart Citations
“…The substances used as target analytes in this study were proposed in a previous study as MOAH markers (Jaén et al, 2021). Furthermore, these substances were identified by different authors in mineral and crude oil samples.…”
Section: Selection Of Moah Markersmentioning
confidence: 95%
“…In a recent study, Koster et al indicated that when MOH contamination is low, current methodologies cannot reliably conclude whether or not the sample is contaminated (Koster et al, 2020). Therefore, it is necessary to apply additional confirmatory techniques, such as two-dimensional gas chromatography (GCxGC), mass spectrometry, and the identification of chemical markers (Jaén, Domeño, Alfaro, & Nerín, 2021;Moret et al, 2013;Spack et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Atmospheric solids analysis probe mass spectrometry (ASAP-MS) is an easy-to-use, simple, low cost, and rapid ionization technique that enables direct analysis of volatile and semi-volatile solid and liquid samples without the need for any sample preparation and solvents. [12][13][14][15] The temperature ramp applied in ASAP-MS allows volatilizing components according to their boiling points, with no chromatographic separation. In addition, it is efficient of ionizing low polarity molecules not responsive to ESI-MS and atmospheric pressure chemical ionization (APCI) at high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric solids analysis probe mass spectrometry (ASAP‐MS) is an easy‐to‐use, simple, low cost, and rapid ionization technique that enables direct analysis of volatile and semi‐volatile solid and liquid samples without the need for any sample preparation and solvents 12–15 . The temperature ramp applied in ASAP‐MS allows volatilizing components according to their boiling points, with no chromatographic separation.…”
Section: Introductionmentioning
confidence: 99%